FAMILY SUPPORT BERHUBUNGAN DENGAN KEPATUHAN MINUM OBAT PADA PASIEN TUBERCULOSIS DI WILAYAH KERJA PUSKESMAS KEBONSARI KOTA SURABAYA - Aries Chandra Anandhita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: ComplianceÂ Â withÂ Â takingÂ Â medicationÂ Â isÂ Â stillÂ Â aÂ Â problemÂ Â thatÂ Â oftenoccurs in the treatment of tuberculosis patients, so that it is not uncommon for patients to take their treatment incomplete, this is evidenced by the percentage of incomplete treatment in Indonesia which is 13% and in the city of Surabaya itself is 44.6%. For this reason, good family support is needed to improve medication adherence. This study aims to analyze the relationship between family support and medication adherence in tuberculosis patients in the working area of the Kebonsari Public Health Center, SurabayaMethods: The research method uses a correlation analytic design with a cross sectional approach. The sample in this study was 30 respondents who were in the working area of the Kebonsari Health Center. Sampling using Non Probability Sampling with Total Sampling sampling technique. The research instrument used a family support and compliance questionnaire. Data analysis used the Spearman Rank Test correlation test with the help of SPSS 23.Results: The results of the univariate analysis showed that the characteristics of each variable measured were gender (46.7% male; 53.3% female), education (40% elementary school; 33.3% junior high school; 16.7% senior high school; 10% undergraduate), andÂ Â Â employmentÂ Â Â (mostlyÂ Â Â householdÂ Â Â andÂ Â Â private households, namely 33,3%). The results of the bivariate analysis showed that thereÂ Â wasÂ Â aÂ Â strongÂ Â relationshipÂ Â betweenÂ Â familyÂ Â supportÂ Â andÂ Â adherenceÂ Â to medication in tuberculosis patients in the working area of the Kebonsari Health Center (Ï = 0.000 < = 0.05 with a correlation value of 0.622), meaning that there was a strong relationship and a positive relationship, the better. Family support, the better the adherence to taking medication for TB patients, namely respondents who have good compliance as many as 14 respondents (46.7%) and as many as 21 respondents (70%) have good family support.Conclusion:Â Therefore, families are expected to accompany patients for treatment to the puskesmas, pay attention to the patient's food and daily needs, remind patients when it is time to take medicine (PMO), give love and affection, and support patients to remain optimistic about their recovery and remind them to always pray to God for healing. given healing.